High-performance composite film and preparation method thereof

By constructing a composite film with a gradient structure on the surface of the metal substrate, using a high-entropy alloy layer, a boride or nitride layer and a carbide layer, and doping silicon, nitrogen and fluorine elements on the surface of the carbide layer, the problem that the prior art is difficult to meet the various performance requirements of metal components under extreme conditions at the same time, and the preparation of a high-performance composite film is realized.

CN119710593APending Publication Date: 2025-03-28YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411920812.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing coating technology is difficult to meet the comprehensive performance of high temperature resistance, corrosion resistance, high strength and low friction coefficient required by metal components under extreme conditions.

Method used

A high-entropy alloy layer is used as the transition layer, a boron or nitride layer and a carbide layer are used as the intermediate layer, and a functional optimization layer is formed on the surface of the carbide layer to form a functional optimization layer to build a composite film with a gradient structure.

Benefits of technology

The high performance performance of composite films under extreme conditions is achieved, including high hardness, wear resistance, corrosion resistance and low friction coefficient, extending the service life of metal devices and improving performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710593A_ABST
    Figure CN119710593A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal surface protection, in particular to a high-performance composite film and a preparation method thereof.The composite film comprises a transition layer, a middle layer and a function optimization layer which are sequentially arranged on the surface of a metal substrate from inside to outside, the transition layer is a high-entropy alloy layer, the middle layer contains a boride layer or a nitride layer and a carbide layer, and the function optimization layer is a high-entropy alloy layer. The function optimization layer is a film layer formed by doping at least one of silicon, nitrogen and fluorine on the surface of the carbide layer; the preparation method comprises the following steps: pretreating until the surface roughness Ra of the metal substrate is 0.05-0.2 mu m; ion beam bombardment strengthening is conducted, and then a high-entropy alloy layer is formed through a magnetron sputtering method; the middle layer is formed through combination of a magnetron sputtering method and a laser interference technology, and then the function optimization layer is formed through PECVD (Plasma Enhanced Chemical Vapor Deposition). The obtained composite film is resistant to high temperature and corrosion, high in strength and low in friction coefficient, and can be used in extreme working conditions; the preparation method provided by the invention has good operability and repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface protection, in particular to a high-performance composite film and a preparation method thereof. Background Art

[0002] With the rapid development of industry, the improvement of the surface properties of metal materials is of great significance for enhancing product performance and extending service life. In the fields of aerospace, automobile manufacturing, medical equipment, etc., metal parts are often used in extreme conditions such as high temperature, high humidity, strong acid and alkali environment and long-term wear conditions. Therefore, how to make metal parts maintain good stability and reliability under the above extreme conditions is crucial. To this end, emerging coating technologies, such as magnetron sputtering and chemical vapor deposition, have been explored. Although significant progress has been made in improving the density and uniformity of the coating, it still faces a series of challenges. In particular, the films obtained by emerging coating technologies are still difficult to simultaneously meet the multiple comprehensive properties required under extreme conditions such as high temperature resistance, corrosion resistance, high strength and low friction coefficient, which restricts its use and promotion in a wider range of fields.

[0003] To this end, this application is filed. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-performance composite film and a preparation method thereof, aiming to improve the service life and performance stability of metal devices in harsh environments.

[0005] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0006] On the one hand, the present invention proposes a high-performance composite film, which is arranged on the surface of a metal substrate, including: a transition layer, an intermediate layer and a function optimization layer, which are arranged in sequence from the inside to the outside of the metal substrate surface, wherein the transition layer is a high entropy alloy layer, the intermediate layer contains a boride layer or a nitride layer and a carbide layer, the boride layer or the nitride layer is arranged adjacent to the high entropy alloy layer, and the function optimization layer is a film layer formed by doping the surface of the carbide layer with at least one of silicon, nitrogen and fluorine elements.

[0007] A high entropy alloy layer is used as a transition layer, which has the properties of high strength, high hardness, high temperature resistance, wear resistance, corrosion resistance, etc. It has good adhesion to the metal substrate and can be firmly attached to the surface of the metal substrate to create stable adhesion conditions for the intermediate layer, effectively alleviate the stress caused by the difference in thermal expansion coefficient between the coating and the substrate, and improve the stability and durability of the coating; a boride layer or a nitride layer and a carbide layer are arranged in sequence, and the performance gradually transitions to obtain an intermediate layer with a gradient structure, further improving the film layer including strength, hardness, high temperature resistance, wear resistance, corrosion resistance and other properties, and enhancing the bonding force between the film layer and the metal substrate; on this basis, the surface of the carbide layer of the intermediate layer is further doped with elements to form a functional optimization layer, which stabilizes the structure and performance of the composite film and optimizes the appearance of the composite film while realizing the regulation of specific properties, such as doping with silicon to improve hardness, wear resistance and corrosion resistance, doping with nitrogen to improve hardness and wear resistance, and doping with fluorine to reduce the friction coefficient. The present invention obtains a composite film layer with good comprehensive performance through simple film layer structure design and mutual influence and synergistic effect among three film layers. The composite film layer has high temperature resistance, corrosion resistance, high strength and low friction coefficient and can meet the use requirements under extreme conditions.

[0008] Preferably, the high entropy alloy layer is selected from any one of MoZrNbTiHf, CrAlTiSiV, FeCoNi CuZn; and the intermediate layer is selected from any one of ZrB2 / HfC, NbN / TaC, and BN / SiC.

[0009] Preferably, the thickness requirements of each layer are as follows:

[0010] The thickness of the high entropy alloy layer is 0.3-1.0 μm. This thickness range can effectively improve the surface state of the metal substrate and provide a good adhesion basis for the intermediate layer and the function optimization layer, but will not introduce excessive stress due to excessive thickness and thus affect other properties;

[0011] The thickness of the intermediate layer is 1.5-3.5 μm and the thickness ratio of the boride layer or the nitride layer to the carbide layer is 1:(1-3). The design of this thickness ratio and total thickness helps to achieve a gradual transition in performance from the transition layer to the function optimization layer, effectively disperse stress, and improve the overall hardness, wear resistance and corrosion resistance of the film layer;

[0012] The thickness of the functional optimization layer is 0.1-0.5 μm. This thickness range can ensure the optimization of various properties such as hardness, wear resistance, corrosion resistance, surface roughness, glossiness, etc., while avoiding problems such as excessive internal stress and decreased film adhesion caused by excessive thickness.

[0013] Preferably, the transition layer is MoZrNbTiHf, the intermediate layer is ZrB2 / HfC, the functional optimization layer is a film layer formed by doping silicon element on the surface of HfC, and the thicknesses of the transition layer, the intermediate layer, and the functional optimization layer are 0.6 μm, 2.5 μm, and 0.3 μm, respectively.

[0014] MoZrNbTiHf is a high-entropy alloy material with high strength, high hardness, good corrosion resistance, excellent high-temperature stability and oxidation resistance, good plasticity and formability. As a transition layer, it can not only firmly adhere to the surface of various metal substrates, but also provide a stable adhesion basis for the intermediate layer, promote the diffusion and deposition of atoms in the intermediate layer and the functional optimization layer, and make the entire composite membrane structure more compact.

[0015] ZrB2 is a typical ultra-high temperature ceramic material with the characteristics of high melting point, high hardness, high thermal conductivity and low thermal expansion coefficient. It has the dual characteristics of ceramics and metals, and has excellent high hardness and high-temperature chemical stability. HfC is also a typical ultra-high temperature ceramic material, which not only has excellent high hardness and high-temperature chemical stability, but also has more excellent oxidation resistance and corrosion resistance. The gradient structure intermediate layer formed by ZrB2 and HfC with a specific thickness ratio not only helps to exert their respective advantages, but also can achieve a synergistic improvement in performance. Moreover, the present application unexpectedly found that ZrB2 is set near MoZrNbTiHf, which can significantly improve the yield strength and ultimate compression strength of MoZrNbTiHf. It is speculated that on the one hand, it may be because the B element has the effect of refining the alloy grains, making the grain boundaries clearer, thereby increasing the strength of MoZrNbTiHf; on the other hand, it may be that B atoms form interstitial solid solutions in MoZrNbTiHf, further improving the solid solution strengthening effect of the alloy. In addition, although BN also contains B element which can refine grains, its effect as a nitride layer adjacent to MoZrNbTiHf is not as good as that of ZrB2. It may be that Zr helps to improve the strength and overall stability of MoZrNbTiHf, while N can improve the hardness and wear resistance of MoZrNbTiHf, but will increase the brittleness of MoZrNbTiHf. Therefore, for extreme environments such as high temperature, high pressure, and high cold, the introduction of Zr is more effective than the introduction of N.

[0016] The functional optimization layer formed by introducing silicon elements on the surface of the carbide layer in the middle layer has a better effect. The reason for this is that there is a strong interatomic bonding force between the silicon elements and the carbon elements in the carbide layer, which will have the following effects on the microstructure of the film layer: (1) Silicon and carbon form a more stable lattice structure. This lattice matching helps to reduce the interfacial stress between the composite film layers and improve the stability of the film layer; (2) The strong interatomic bonding force between silicon and carbon makes the composite film structure denser, which helps to reduce the pores and defects of the composite film, improve the hardness and wear resistance, beautify the appearance, and reduce the friction coefficient; moreover, it is also possible that part of the silicon and carbon combine in situ to form silicon carbide, which is a compound with high hardness, high wear resistance and high corrosion resistance. It is dispersed in the functional optimization layer, further enhancing the overall performance of the composite film.

[0017] The present invention accidentally discovered that when the thickness ratio of the transition layer, the intermediate layer, and the function optimization layer is 6:25:3, the performance of the obtained composite film is optimal. It is speculated that the synergistic effect of the performance between the film layers that meet this thickness relationship is maximized.

[0018] Compared with the prior art, the high-performance composite membrane proposed in the present invention has the following advantages: (1) strong bonding force with the metal substrate, no peeling or falling off will occur after being tested under extreme conditions such as high temperature 400-800°C, high humidity 85%-95%RH and strong acid and alkali pH 2-12, the composite membrane has strong adhesion, performance fluctuation is no more than 3%, and the composite membrane performance is stable; (2) it has high hardness, high wear resistance and fatigue resistance, and exhibits good durability and service life under heavy load and long-term wear environment; (3) it has strong corrosion resistance and oxidation resistance, and the corrosion rate and performance degradation are small in various corrosive environments such as strong acid, strong alkali, salt spray, high temperature oxidation and industrial waste gas, which helps to provide long-term protection for the metal substrate; (4) it has high thermal stability and strong environmental applicability. The composite membrane exhibits stable thermal stability within 800°C and has small performance fluctuation, so it can adapt to various working conditions from low temperature to high temperature. Therefore, it has stable performance and long service life in harsh environments. In addition, it has small surface roughness, good glossiness, good appearance and fluid mechanics properties and functional integration characteristics. By controlling the doping of specific elements, the functional optimization layer not only improves the overall performance of the composite film but also has high insulation, high transmittance and good biocompatibility. It can meet the use requirements in the fields of electronics, optics, medical equipment, etc., thus expanding the application areas of coated metals.

[0019] On the other hand, the present invention provides a method for preparing a high-performance composite membrane, comprising the following steps:

[0020] S1. Pre-treat the surface of the metal substrate including at least degreasing, pickling and polishing. Fine pre-treatment can optimize the surface state of the metal substrate and provide a high-quality surface foundation for the subsequent coating process. The roughness Ra of the metal substrate surface after pre-treatment is 0.05-0.2μm;

[0021] S2, firstly subjecting the metal substrate obtained in the previous step to ion beam bombardment strengthening to further optimize the surface microstructure of the metal substrate, and then forming the high entropy alloy layer on the surface thereof by magnetron sputtering;

[0022] S3. First, the intermediate layer is formed on the high entropy alloy layer by a magnetron sputtering method combined with laser interference technology, and then at least one of silicon, nitrogen and carbon elements is introduced into the carbide layer by plasma enhanced chemical vapor deposition to form the function optimization layer.

[0023] It should be noted that:

[0024] The pretreatment described in step S1 can accurately control the surface roughness of the metal substrate to 0.05-0.2 μm after the treatment. The metal substrate has a roughness in this range. On the one hand, it can provide a suitable surface morphology for subsequent coating, increase the contact area between the metal substrate and the high entropy alloy layer, and make the high entropy alloy layer firmly adhere thereto. On the other hand, it can optimize the film performance. During the formation process, the high entropy alloy layer can better fill the microscopic concave-convex of the metal substrate surface, reduce stress concentration, and facilitate better adhesion and bonding of the intermediate layer and the functional optimization layer. Under the synergistic effect, the hardness, wear resistance and corrosion resistance of the entire composite film are improved.

[0025] The ion beam bombardment strengthening described in step S2 is specifically performed by bombarding the metal substrate surface with an ion beam generated by a high-energy pulsed ion source to further optimize the surface morphology of the metal substrate. The ion beam bombardment of the metal substrate surface is mainly used to improve the adhesion of the film layer, improve the coverage of the film layer, improve the coating quality and deposition rate. The present invention unexpectedly found that ion beam bombardment of the metal substrate surface with a surface roughness Ra of 0.05-0.2μm after pretreatment has a very obvious effect on improving the coating quality and coating process stability, the process has good repeatability, and the obtained composite film has good consistency, which can better meet the extremely high requirements for the quality and performance of the coating in specific applications such as aerospace and electronics.

[0026] Preferably, the method further includes operation step S4: low-temperature plasma treatment and sealing treatment, wherein the low-temperature plasma treatment is performed using gases such as oxygen, nitrogen, and argon, which helps to further improve the stability of the composite membrane and increase its activity; the sealing treatment uses silicone solution or fluorocarbon polymer solution for dipping or spraying, and low-temperature curing to form a dense protective film. The presence of the protective film can effectively prevent the intrusion of corrosive media and make the surface of the composite membrane smoother and more uniform, thereby further improving the performance of the composite membrane while extending its service life and enhancing its aesthetics, thereby ensuring the reliability and stability of the composite membrane when used in specific high-requirement fields.

[0027] Preferably, in order to obtain a good sealing effect, the present invention has verified through several experiments that when the organic silicon solution is used for impregnation, the impregnation time is 10-60 minutes and the temperature is 30-80°C; when the fluorocarbon polymer solution is used for spraying, the spraying amount is 0.1-0.5L / m 2 The spraying temperature is 15-35℃ and the pressure is 0.3-0.6MPa; the low-temperature curing temperature is 80-150℃ and the time is 10-60min.

[0028] Preferably, in step S1:

[0029] The specific operation of the degreasing is: first, the metal substrate is placed in a degreasing agent at 60-80° C. and soaked for 15-30 minutes, wherein the degreasing agent is an aqueous solution with a concentration of 8wt%-15wt% prepared by sodium citrate and sodium gluconate in a mass ratio of 1:(0.5-2), and the degreasing agent is an environmentally friendly degreasing agent, and then taken out and sprayed with 0.3-0.6MPa high pressure of normal temperature water to remove the degreasing agent remaining on the surface, and then rinsed with hot water and normal temperature water in sequence to completely remove the degreasing agent; the degreasing treatment is used to achieve deep cleaning of the metal substrate;

[0030] The specific operation of the pickling is: first, the metal substrate is placed in a diluted solution of a corrosion-inhibiting pickling solution at 50-70°C and immersed for 8-15 minutes, wherein the components of the corrosion-inhibiting pickling solution are: H2SO4 5wt%-30wt%, H3PO4 10wt%-40wt% and citric acid 20wt%-60wt%, and the concentration of the diluted solution is 8wt%-15wt%; compared with the traditional pickling solution, the corrosion-inhibiting pickling solution can slow down the corrosion rate and corrosion degree, keep the surface flat, enhance the adhesion of the coating, and improve the gloss of the product; further, ultrasonic assisted oscillation is performed during the acidification process to ensure uniform corrosion, and the frequency of the ultrasonic wave is preferably 20-40kHz; after the acidification is completed, the metal substrate is taken out and neutralized with a weak alkaline buffer solution, and then rinsed with water and vacuum dried; the purpose of the pickling is to preliminarily form a microstructure suitable for coating on the surface of the metal substrate;

[0031] The specific operation of the polishing is: polishing the metal substrate with a nano-grade polishing agent combined with a high-precision polishing machine until the roughness Ra reaches 0.05-0.2 μm, and then ultrasonically cleaning it with deionized water with a resistivity of ≥18 MΩ·cm for 10-15 minutes, and the ultrasonic frequency is preferably 40-60 kHz (it can also be assisted by cavitation cleaning technology to further improve the cleaning effect), and then taking it out and drying it under vacuum; the purpose of the polishing is to obtain a metal substrate with a target roughness.

[0032] Preferably, in step S2, the ion beam generated by the high-energy pulse ion source bombards the surface of the metal substrate, with a pulse current of 0.5-0.8A, a voltage of 300-5000V, an air flow of 30-150sccm, a time of 10-40min, and a frequency of 10-100Hz; when the high entropy alloy layer is formed on its surface by magnetron sputtering, the voltage is 300-5000V, the current is 0.5-0.8A, and the pressure is 5×10 -4 -5×10 -2 Pa, deposition temperature 200-600℃.

[0033] Preferably, in step S3, when forming the intermediate layer, the sputtering power is 300-1500W, the temperature is 200-500°C, when forming the functional optimization layer, the RF power is 150-350W, the carbon source gas flow rate is 8-35sccm, the working gas pressure is 25-50Pa, the silicon source is SiH4, the nitrogen source is N2 or NH3, and the fluorine source is F2 or CHF3.

[0034] Compared with the prior art, the present invention first provides a high-quality surface foundation for coating by finely pre-treating the metal substrate, then performs ion beam bombardment strengthening, forms a high entropy alloy layer by magnetron sputtering, then forms an intermediate layer by magnetron sputtering combined with laser interference technology, and finally forms a functional optimization layer by PECVD, and finally constructs a composite film layer with simple structure and good comprehensive performance on the metal surface. The preparation method proposed by the present invention has a small process flow, strong operability, good repeatability, and the obtained composite film has uniform and consistent performance, which can ensure the long-term, stable and reliable use of metal devices in extremely complex environments, and provides reliable technical support for the application of coated metals in various fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0036] Figure 1These are photos of the Haynes 25 cobalt alloy plate after coating in Example 1 of the present invention: the left photo is a real photo, and the right photo is a photo magnified 50,000 times.

[0037] Figure 2 These are photos of the 5052 aluminum alloy plate after coating in Example 2 of the present invention: the left photo is a real photo, and the right photo is a photo magnified 50,000 times.

[0038] Figure 3 These are photos of the Nitinol 55 nickel-titanium alloy plate after coating in Example 3 of the present invention: the left photo is a real photo, and the right photo is a photo magnified 50,000 times. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0040] The pretreatment used in the following embodiments and comparative examples specifically includes: degreasing, pickling and polishing. The specific operation of degreasing is: first, the metal substrate is immersed in a degreasing agent at 70°C for 20 minutes. The degreasing agent is a 12wt% aqueous solution prepared by sodium citrate and sodium gluconate in a mass ratio of 1:1.8. The degreasing agent is an environmentally friendly degreasing agent. Then, it is taken out and sprayed with 0.5MPa high pressure of normal temperature water to remove the degreasing agent remaining on the surface, and then rinsed with hot water and normal temperature water in sequence to completely remove the degreasing agent; the specific operation of the acid is: first, the metal substrate is immersed in a dilution of a corrosion-inhibiting pickling solution at 60°C for 10 minutes. The components of the corrosion-inhibiting pickling solution are: H2SO4 20wt%, H3PO4 25wt% and 55wt% citric acid, the concentration of the dilution is 12wt%, and 30kHz ultrasound is used for ultrasonic-assisted oscillation during the acidification process; after the acidification is completed, the metal substrate is taken out and neutralized with a weakly alkaline sodium dihydrogen phosphate buffer solution, then rinsed with water and vacuum dried at 150°C for 25min; the specific operation of the polishing is: polishing the metal substrate with a nano-grade polishing agent combined with a high-precision polishing machine until the roughness is reached, and then ultrasonically cleaning it with deionized water with a resistivity of ≥18MΩ·cm for 15min, the ultrasonic frequency is 50kHz, and then taking it out and vacuum drying it at 140°C for 20min.

[0041] The technical parameters of the low-temperature plasma treatment used in the following examples and comparative examples are: oxygen, air pressure 80Pa, power 100W, time 20min. The sealing treatment performed in the following examples and comparative examples: the specific components of the organic silicon solution used are: 35wt% alkyl silanol, 12wt% quaternary ammonium silanol, 18wt% ethyl silicate, 25wt% water, 2wt% organic tin catalyst, 8wt% curing agent amino resin. When the organic silicon solution is used for impregnation, the immersion time is 30min and the temperature is 50°C; the specific components of the fluorocarbon polymer solution used are: 55wt% fluorocarbon resin, 30wt% acetone, 2wt% organic silicon leveling agent, 1wt% polyether modified siloxane, 4wt% silane coupling agent, 8wt% titanium dioxide. When the fluorocarbon polymer solution is used for spraying, the spraying amount is 0.3L / m 2 , spraying temperature is 24℃, pressure is 0.5MPa; low temperature curing temperature is 110℃, time is 30min.

[0042] The test conditions of the various properties involved in the following embodiments and comparative examples are as follows: Adhesion test: According to GB / T 9286-2021 standard, and add harsh conditions, including: the scratch depth reaches 25% of the substrate thickness, and the cross angle is randomly set (30°-90°). Extreme environment durability: Placed in high temperature 800°C, high humidity 95% RH, and strong acid and alkali environment pH 2 for 24 hours respectively. Hardness value: Measured jointly by nanoindenter and atomic force microscope. Hardness uniformity: The microhardness fluctuation is controlled within the range of ±50HV. Wear resistance: (1) Ball-disc friction and wear test, on a high-speed ball-disc testing machine, load 10N, speed 800r / min, wear time 6h; (2) Three-body wear test: Use SiC particles as abrasive, concentration 12%, load 10N, wear time 5h. Corrosion resistance: (1) Salt spray test, according to GB / T 10125-2021 standard, and by increasing the spray pressure (1.5 times) and temperature (70°C); (2) Simulated acid rain environment: pH 2, immersion for 1200h. High temperature oxidation test: in a high temperature environment of 850°C, oxidation time for 600h. Surface roughness: tested using an atomic force microscope. Gloss: tested by a gloss meter.

[0043] It should be noted that the operations or raw materials not described in detail below are all conventional techniques in the art and can be obtained by those skilled in the art without creative effort.

[0044] Example 1

[0045] A high-performance composite film is arranged on the surface of a Haynes 25 cobalt alloy plate, comprising: a transition layer, an intermediate layer and a function optimization layer arranged in sequence from the inside to the outside of the surface, wherein the transition layer is MoZrNbTiHf with a thickness of 0.6 μm, the intermediate layer is ZrB2 / HfC with a total thickness of 3.5 μm, wherein the thickness of ZrB2 is 1 μm, and the thickness of HfC is 2.5 μm, and the function optimization layer is a film layer with a thickness of 0.2 μm formed by doping silicon on the surface of HfC.

[0046] The preparation method of the high performance composite film is specifically as follows:

[0047] S1. Pre-treating the surface of the Haynes 25 cobalt alloy plate until the roughness Ra is 0.1 μm;

[0048] S2, the metal substrate obtained in the previous step is first subjected to ion beam bombardment strengthening, with the parameters set as pulse current 0.6A, voltage 4000V, gas flow 80sccm, processing time 25min, frequency 50Hz, and then the high entropy alloy layer is formed on its surface by magnetron sputtering, with the parameters set as voltage 4000V, current 0.6A, gas pressure 2×10-3Pa, and deposition temperature 400°C;

[0049] S3, firstly forming the intermediate layer on the high entropy alloy layer by magnetron sputtering combined with laser interference technology, the sputtering power is 800W, and the deposition temperature is 350°C; then introducing silicon into the carbide layer by plasma enhanced chemical vapor deposition PECVD to form the functional optimization layer, the silicon source is SiH4, and the parameters are set to RF power 250W, silicon source gas flow rate 20sccm, and working gas pressure 35Pa;

[0050] S4, firstly perform low temperature plasma treatment, and then perform pore sealing treatment with organic silicon solution.

[0051] After testing: Finally, we get Figure 1 The high-performance composite film shown has a hardness of HV3000, a surface roughness Ra of less than 0.025 μm, and a corrosion rate of less than 0.003 mm / a.

[0052] Example 2

[0053] A high-performance composite film is arranged on the surface of a 5052 aluminum alloy plate, comprising: a transition layer, an intermediate layer and a function optimization layer arranged in sequence from the inside to the outside of the surface, wherein the transition layer is CrAlTiSiV with a thickness of 0.5 μm, the intermediate layer is NbN / TaC with a total thickness of 2 μm, wherein the thickness of NbN is 1 μm, and the thickness of TaC is 1 μm, and the function optimization layer is a film layer with a thickness of 0.3 μm formed by doping fluorine on the surface of HfC.

[0054] The preparation method of the high performance composite film is specifically as follows:

[0055] S1. Pre-treat the surface of the 5052 aluminum alloy plate until the roughness Ra is 0.05 μm;

[0056] S2, the metal substrate obtained in the previous step is first subjected to ion beam bombardment strengthening, with the parameters set as pulse current 0.7A, voltage 3500V, gas flow 100sccm, processing time 30min, frequency 75Hz, and then the high entropy alloy layer is formed on its surface by magnetron sputtering, with the parameters set as voltage 3500V, current 0.7A, gas pressure 1×10-3Pa, and deposition temperature 300°C;

[0057] S3, firstly forming the intermediate layer on the high entropy alloy layer by magnetron sputtering combined with laser interference technology, the sputtering power is 1000W, and the deposition temperature is 400°C; then introducing fluorine into the carbide layer by plasma enhanced chemical vapor deposition method PECVD to form the functional optimization layer, the fluorine source is CHF3, and the parameters are set to RF power 350W, fluorine source gas flow rate 35sccm, and working gas pressure 50Pa;

[0058] S4. Firstly perform low-temperature plasma treatment, and then spray fluorocarbon polymer solution for pore sealing.

[0059] After testing: Finally, we get Figure 2 The high-performance composite film shown has a hardness of HV2900, a surface roughness Ra of less than 0.03 μm, and an acid rain test corrosion rate of less than 0.004 mm / a.

[0060] Example 3

[0061] A high-performance composite film is arranged on the surface of Nitinol 55 nickel-titanium alloy, including: a transition layer, an intermediate layer and a function optimization layer arranged in sequence from the inside to the outside of the surface, the transition layer is FeCoNiCuZn with a thickness of 1μm, the intermediate layer is BN / SiC with a total thickness of 2.5μm, wherein the BN thickness is 0.6μm and the SiC thickness is 1.9μm, and the function optimization layer is a film layer with a thickness of 0.15μm formed by doping nitrogen on the surface of HfC.

[0062] The preparation method of the high performance composite film is specifically as follows:

[0063] S1. Pre-treating the surface of Nitinol 55 nickel-titanium alloy until the roughness Ra is 0.2 μm;

[0064] S2, the metal substrate obtained in the previous step is first subjected to ion beam bombardment strengthening, with the parameters set as pulse current 0.8A, voltage 5000V, gas flow 150sccm, processing time 40min, frequency 100Hz, and then the high entropy alloy layer is formed on its surface by magnetron sputtering, with the parameters set as voltage 5000V, current 0.8A, gas pressure 5×10-2Pa, and deposition temperature 600°C;

[0065] S3, firstly forming the intermediate layer on the high entropy alloy layer by magnetron sputtering combined with laser interference technology, the sputtering power is 1000W, and the deposition temperature is 450°C; then introducing nitrogen into the carbide layer by plasma enhanced chemical vapor deposition method PECVD to form the functional optimization layer, the nitrogen source is N2, and the parameters are set as RF power 200W, nitrogen source gas flow rate 15sccm, and working gas pressure 40Pa;

[0066] S4, firstly perform low temperature plasma treatment, and then perform pore sealing treatment with organic silicon solution.

[0067] After testing: Finally, we get Figure 3 The high-performance composite film shown has a hardness of HV2950, ​​a surface roughness Ra of less than 0.04 μm, and a corrosion rate of less than 0.003 mm / a.

[0068] Example 4

[0069] Compared with Example 1, the thickness of the transition layer MoZrNbTiHf is adjusted to 0.3 μm. The rest is the same as Example 1.

[0070] Example 5

[0071] Compared with Example 1, the total thickness of the intermediate layer is adjusted to 1.5 μm, of which the thickness of ZrB2 is 0.5 μm and the thickness of HfC is 1 μm. The rest are the same as in Example 1.

[0072] Example 6

[0073] Compared with Example 1, the thickness of the function optimization layer is adjusted to 0.1 μm. The rest is the same as Example 1.

[0074] Example 7

[0075] Compared with Example 1, the thickness of the function optimization layer is adjusted to 0.5 μm. The rest is the same as Example 1.

[0076] Example 8

[0077] Compared with Example 1, step S4 is not performed. The rest is the same as Example 1.

[0078] Keeping the same test conditions as in Example 1, the corrosion rate is 0.005-0.007 mm / a. Obviously, the protective film formed by the sealing treatment can effectively isolate the external environment from corroding the surface of the composite membrane.

[0079] Example 9

[0080] Compared with Example 1, the thickness of the function optimization layer is adjusted to 0.15 μm. The rest is the same as Example 1.

[0081] Example 10

[0082] Compared with Example 1, the thickness of the function optimization layer is adjusted to 0.3 μm. The rest is the same as Example 1.

[0083] Embodiment 11

[0084] Compared with Example 1, the thickness of the function optimization layer is adjusted to 0.4 μm. The rest is the same as Example 1.

[0085] After testing and comparison, the hardness of Example 9, Example 1, Example 10, and Example 11 are HV2800, HV3000, HV3200, HV3500, and HV3100, respectively. The thickness of the function optimization layer shown in Example 10 is more conducive to obtaining a composite film with high hardness. Further testing found that the wear resistance and corrosion resistance of Example 10 are also excellent: the ball-disc friction wear rate is 0.15×10 -7 mm 3 / N·m, the three-body wear rate is 0.3×10 -7 mm 3 / N·m; in the salt spray test, the slightly corroded area accounts for less than 2%, and the corrosion rate in the acid rain test is less than 0.003mm / a.

[0086] Example 12

[0087] Compared with Example 1, the function optimization layer is adjusted to fluorine doping, the fluorine source is CHF3, the parameters are set to RF power 350W, fluorine source gas flow rate 35sccm, and working gas pressure 50Pa. The rest are the same as Example 1.

[0088] Embodiment 13

[0089] Compared with Example 1, the function optimization layer is adjusted to nitrogen doping, the nitrogen source is N2, and the parameters are set to RF power 200W, nitrogen source gas flow rate 15sccm, and working gas pressure 40Pa. The rest are the same as Example 1.

[0090] After testing and comparison, among the products obtained from Example 1, Example 12, and Example 13, Example 1 has the highest hardness, Example 13 has the best wear resistance, and Example 12 has the lowest friction coefficient.

[0091] Embodiment 14

[0092] Compared with Example 1, the transition layer MoZrNbTiHf is adjusted to CrAlTiSiV. The rest is the same as Example 1.

[0093] Embodiment 15

[0094] Compared with Example 1, the transition layer MoZrNbTiHf is adjusted to FeCoNiCuZn. The rest is the same as Example 1.

[0095] The products obtained in Example 1, Example 14 and Example 15 were subjected to a rotating disc friction and wear test and a three-body wear test. The test results showed that Example 1 was the best, and its ball-disc friction and wear rate was 0.22×10 -7 mm 3 / N·m, and its three-body wear rate is 0.4×10 -7 mm 3 / N·m.

[0096] The adhesion test results of Examples 1 to 15 showed that the adhesion reached level 0-1; the extreme environment durability test results showed that the adhesion remained at level 0-1; the hardness value was HV2500-HV3500, and the microhardness fluctuation was within ±50HV; the ball-disc friction and wear test results showed that the wear rate was 0.15×10 -7 -0.4×10 -7 mm 3 / N·m; the three-body wear test results show that the wear rate is less than 0.3×10 -7 -0.8×10 -7 mm 3 / N·m; the salt spray test shows that the surface area of ​​the composite film with slight corrosion accounts for no more than 5%, and the acid rain test shows that its corrosion rate is lower than 0.006mm / a; the high temperature oxidation test shows that its corrosion rate is lower than 0.006mm / a; the surface roughness test shows that its Ra≤0.05μm; the gloss test results show that the minimum gloss is 90. Obviously, the high-performance composite film prepared by the preparation method proposed in the present invention has excellent performances, and the performance fluctuation is very small under extreme working conditions, which can meet the use needs.

[0097] Comparative Example 1

[0098] Compared with Example 1, the thickness of the transition layer MoZrNbTiHf is adjusted to 0.2 μm. The rest is the same as Example 1.

[0099] Comparative Example 2

[0100] Compared with Example 1, the thickness of the transition layer MoZrNbTiHf is adjusted to 1.5 μm. The rest is the same as Example 1.

[0101] The products obtained in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to thermal cycle tests. The test results showed that after 10 cycles at 500°C, the coating of Example 1 remained intact, while Comparative Example 1 and Comparative Example 2 had local cracks. It is speculated that Comparative Example 1 should be due to the fact that the transition layer is too thin, which cannot provide a good adhesion foundation for the intermediate layer and the function optimization layer; while Comparative Example 2 should be due to the fact that the transition layer is too thick, resulting in greater stress. Obviously, a transition layer that is too thick or too thin is not conducive to the stability and integrity of the composite film adhesion.

[0102] Comparative Example 3

[0103] Compared with Example 1, the thickness of the function optimization layer is adjusted to 0.05 μm. The rest is the same as Example 1.

[0104] Comparative Example 4

[0105] Compared with Example 1, the thickness of the function optimization layer is adjusted to 0.8 μm. The rest is the same as Example 1.

[0106] Comparative Example 5

[0107] Compared with Example 1, the total thickness of the intermediate layer is adjusted to 0.9 μm, of which the thickness of ZrB2 is 0.3 μm and the thickness of HfC is 0.6 μm. The rest are the same as in Example 1.

[0108] Comparative Example 6

[0109] Compared with Example 1, the total thickness of the intermediate layer is adjusted to 4.2 μm, of which the thickness of ZrB2 is 1.4 μm and the thickness of HfC is 2.8 μm. The rest are the same as in Example 1.

[0110] The products obtained in Example 5, Example 1, Comparative Example 5 and Comparative Example 6 were tested for hardness, wear resistance and corrosion resistance. The test results showed that the order of the three properties was: Example 1> Example 5> Comparative Example 5> Comparative Example 6. Obviously, an intermediate layer with an appropriate thickness can achieve a gradual transition of performance from the transition layer to the function optimization layer and effectively disperse stress. If it is too thin or too thick, it will have an adverse effect on the overall performance of the composite film layer.

[0111] Comparative Example 7

[0112] Compared with Example 1, the roughness after pretreatment is adjusted to Ra 0.02 μm. The rest is the same as Example 1.

[0113] The test shows that the adhesion of the composite film is level 2-3, which drops to level 3-4 after extreme environment treatment, and the composite film partially falls off. Obviously, if the roughness is too small and the substrate surface is too smooth, the mechanical bite between the composite film and the substrate will be weakened, reducing the bonding force between the two. Although the composite film looks smooth, when subjected to external force, the composite film layer can easily peel off from the substrate. In addition, an overly smooth substrate surface will limit atomic diffusion and deposition, resulting in uneven growth of the film layer, affecting the overall performance of the composite film.

[0114] Comparative Example 8

[0115] Compared with Example 1, no pretreatment was performed, and the test showed that the surface roughness was Ra 0.3 μm. The rest was the same as Example 1.

[0116] The test shows that the adhesion of the composite film is level 2-3, which drops to level 3-4 after extreme environment treatment, and a large amount of composite film falls off. Obviously, excessive roughness will make it difficult for the composite film to evenly cover the substrate, resulting in uneven local thickness. In subsequent use, it is very easy to cause problems such as film shedding and decreased adhesion due to external influences. Moreover, excessive roughness will lead to increased stress concentration inside the film layer, which is prone to cracks and defects, making it easy for corrosive media to invade and accelerate the corrosion of the film layer.

[0117] Comparative Example 9

[0118] Compared with Example 1, silicon doping is not performed. The rest is the same as Example 1.

[0119] After testing: the hardness of Comparative Example 3 (functional optimization layer thickness 0.05μm), Example 6 (functional optimization layer thickness 0.1μm), Example 1 (functional optimization layer thickness 0.2μm), Example 7 (functional optimization layer thickness 0.5μm), Comparative Example 4 (functional optimization layer thickness 0.8μm) and Comparative Example 9 (no functional optimization layer is set) are HV2600, HV2700, HV3000, HV3000, HV2900, HV2800, respectively, and the surface roughness Ra is approximately 0.06μm, 0.042μm, 0.023μm, 0.023μm, 0.025μm, 0.07μm, respectively. By comparison, it can be seen that compared with no silicon doping and no function optimization layer, silicon doping within an appropriate range can improve the hardness of the composite film and reduce the roughness, and the hardness increases with the increase of silicon doping amount, and the roughness decreases with the increase of silicon doping amount. However, if the silicon doping exceeds the optimal doping amount, the surface roughness will not be further optimized with the increase of doping amount, but the hardness will deteriorate with the increase of doping amount. Moreover, the adhesion of the composite film of Comparative Example 4 is significantly reduced, which should be due to the fact that the function optimization layer is too thick, resulting in greater internal stress and poor adhesion of the film layer.

[0120] In summary: through the preparation method proposed in the present invention, a high-performance composite film with strong adhesion, small friction coefficient, good wear resistance, corrosion resistance, oxidation resistance, high thermal stability and good environmental adaptability can be obtained with relatively simple operation, good process repeatability and high product quality consistency.

[0121] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A high-performance composite film, arranged on the surface of a metal substrate, characterized in that: The invention comprises: a transition layer, an intermediate layer and a function optimization layer which are arranged in sequence from the inside to the outside of the metal substrate surface, wherein the transition layer is a high entropy alloy layer, the intermediate layer contains a boride layer or a nitride layer and a carbide layer, the boride layer or the nitride layer is arranged adjacent to the high entropy alloy layer, and the function optimization layer is a film layer formed by doping the surface of the carbide layer with at least one of silicon, nitrogen and fluorine elements.

2. The high performance composite membrane according to claim 1, characterized in that: The high entropy alloy layer is selected from any one of MoZrNbTiHf, CrAlTiSiV, and FeCoNiCuZn; The intermediate layer is selected from any one of ZrB2 / HfC, NbN / TaC, and BN / SiC.

3. The high performance composite membrane according to claim 1 or 2, characterized in that: The thickness of the high entropy alloy layer is 0.3-1.0 μm, the thickness of the intermediate layer is 1.5-3.5 μm, the thickness ratio of the boride layer or the nitride layer to the carbide layer is 1:(1-3), and the thickness of the function optimization layer is 0.1-0.5 μm.

4. The high performance composite membrane according to claim 1 or 2, characterized in that: The transition layer is MoZrNbTiHf, the middle layer is ZrB2 / HfC, the function optimization layer is a film layer formed by doping silicon element on the surface of HfC, and the thicknesses of the transition layer, the middle layer, and the function optimization layer are 0.6μm, 2.5μm, and 0.3μm, respectively.

5. A method for preparing a high-performance composite membrane according to any one of claims 1 to 4, characterized in that: The steps are as follows: S1. Pretreatment of the metal substrate surface including at least degreasing, pickling and polishing, wherein the roughness Ra of the metal substrate surface after pretreatment is 0.05-0.2 μm; S2, firstly subjecting the metal substrate obtained in the previous step to ion beam bombardment strengthening, and then forming the high entropy alloy layer on its surface by magnetron sputtering; S3. First, the intermediate layer is formed on the high entropy alloy layer by a magnetron sputtering method combined with laser interference technology, and then at least one of silicon, nitrogen and carbon elements is introduced into the carbide layer by plasma enhanced chemical vapor deposition to form the function optimization layer.

6. The preparation method according to claim 5, characterized in that: The method further comprises an operation step S4: low-temperature plasma treatment and pore sealing treatment, wherein the pore sealing treatment adopts dipping or spraying of an organic silicon solution or a fluorocarbon polymer solution and low-temperature curing.

7. The preparation method according to claim 6, characterized in that: When the organic silicon solution is used for dipping, the dipping time is 10-60 minutes and the temperature is 30-80°C; when the fluorocarbon polymer solution is used for spraying, the spraying amount is 0.1-0.5L / m 2 The spraying temperature is 15-35℃ and the pressure is 0.3-0.6MPa; the low-temperature curing temperature is 80-150℃ and the time is 10-60min.

8. The preparation method according to claim 5, characterized in that: In step S1, the specific operation of degreasing is: first, the metal substrate is immersed in a degreasing agent at 60-80°C, wherein the degreasing agent is an aqueous solution with a concentration of 8wt%-15wt% prepared by sodium citrate and sodium gluconate in a mass ratio of 1:(0.5-2), then taken out and sprayed with normal temperature water under high pressure, and then rinsed with hot water and normal temperature water in sequence; the specific operation of acidity is: first, the metal substrate is immersed in a dilution of a corrosion-inhibiting pickling solution, wherein the components of the corrosion-inhibiting pickling solution are: H2SO4 5wt%-30wt%, H3PO410wt%-40wt% and citric acid 20wt%-60wt%, and the concentration of the dilution is 8wt%-15wt%, and ultrasonic-assisted oscillation is performed, then taken out and neutralized with a weak alkaline buffer solution, then rinsed with water and vacuum dried; the specific operation of polishing is: polishing with a nano-grade polishing agent until the target roughness is reached, then ultrasonically cleaned with deionized water, then taken out and vacuum dried.

9. The preparation method according to claim 5, characterized in that: In step S2, the ion beam generated by the high-energy pulse ion source bombards the surface of the metal substrate, with a pulse current of 0.5-0.8A, a voltage of 300-5000V, an air flow of 30-150sccm, a time of 10-40min, and a frequency of 10-100Hz; when the high entropy alloy layer is formed on the surface by magnetron sputtering, the voltage is 300-5000V, the current is 0.5-0.8A, and the pressure is 5×10 -4 -5×10 -2 Pa, deposition temperature 200-600℃.

10. The preparation method according to claim 5, characterized in that: In step S3, when forming the intermediate layer, the sputtering power is 300-1500W, the temperature is 200-500°C, and when forming the functional optimization layer, the RF power is 150-350W, the carbon source gas flow rate is 8-35sccm, the working gas pressure is 25-50Pa, the silicon source is SiH4, the nitrogen source is N2 or NH3, and the fluorine source is F2 or CHF3.

Citation Information

Cited By

  • TaC / graphite composite material and preparation method thereof

    CN120664906A